2-D Actuator based Shape Memory Alloy using PID controller - Abdulkadhim, Hassan Falah; Hassan, Abdulkareem F.; Abdulaali, Ali H. (Basrah Journal for Engineering Sciences, 2022)
Over the past years, researchers have been focusing on development the robotics and actuation due to increase demand for these applications like industrial engineering, oil industry, healthcare, aerospace … etc. This work involves the design, construction and control of the Shape Memory Alloy (SMA) actuator. The industrial actuator has many characteristics able to be measured, which have an impact on the efficiency and effectiveness of the actuator while the execution of its tasks. The most important measurable characteristics are repeatability and accuracy. The current system typically is using Nitinol (Nickle Titanium Naval Ordinance Lab), which is one of the Shape Memory Alloy that contract when applying specific heat on it, and it can be used as an actuator. This work presents SMA in the shape of a spring to operate and control the accurate position of the 2-D system which containing four SMA springs, two SMA springs for the x -axis and two SMA springs for the y - axis. The theoretical design and calculations for SMA springs have been presented to collect information about the SMA springs. In a practical manner, the SMA spring characteristic like force and displacement were collected by a test bed that was designed and constructs before making the final rig. The setting shape of the SMA spring was presented and done as per the theoretical calculations. In the rig, each axis works as a two-direction actuator, the actuator is not prone to precise position points due to hysteresis and temperature variation. The SMA spring exhibited hysteresis and imprecise pointing, for that employing PID (Proportional Integral Derivative) with tracking mode controller to compensate the hysteresis. PID control system is played a decisive role with tracking mode model that achieves the aim behind the construction of the experimental rig. Good results have been obtained presented in three cases of drawing different shapes.